SPESIASI DAN BIOAVAILABILITAS LOGAM BERAT Cu DAN Zn DALAM TANAH PERTANIAN ORGANIK DAN ANORGANIK - N. W. B. S. Devi; I M. Siaka; K. G. D. Putra (Program Studi Kimia, FMIPA, Universitas Udayana (Program of Study in Chemistry, Faculty of Mathematics and Natural Sciences, Udayana University), Bali, Indonesia, 2019)
Agriculture in Indonesia generaly applies agrochemical to improve the quality and quantity of the products, but the impact is, both lands and their products could be contaminated by pollutans especially heavy metals. This study aimed to determine the total metals, speciation, and bioavailability of Cu and Zn in organic and inorganic agricultural soils in Blahbatuh District, Gianyar Regency. The sequential extraction method was performed to release the bonds of heavy metals in each soil component and the determination of the metal concentration was carried out using AAS. The total metals of Cu and Zn in both organic and inorganic soils indicated that both type of soils were still classified as uncontaminated soils because the metal contents were below the maximum limit allowed. The total contents of Cu and Zn in the organic soil were of 45.3922 mg/kg and 47.7645 mg/kg, respectively, while Cu and Zn in the inorganic soil were 48.9121 mg/kg ??and 49.9474 mg/kg, respectively. Fractination in the organic and inorganic soil EFLE (easly, freely,leachable, and exchangeable), reducible, oxidisable, dan resistant including F4> F3> F2> F1 for Cu and F4> F3> F1> F2 for Zn. The bioavailability of Cu and Zn in the organic soils were 10.52-23.79% and 3.79-7.21% bioavailable, 10.03-25.50% and 14.99-32.68% potentially bioavailable, 38.64-63.19% and 41.20- 60.28% non bioavailable, while in the inorganic soil and were 18.31-32.63% and 4.54-7.85% bioavailable, 9.86-13.85% and 15.26-32.55% potentially bioavailable, and 40.20-59.14% and 42.84-58.26% non bioavailable. Consuquenthy, both types of the agricultural soils would be safe for planting various types of rice. Keywords: bioavailability, Cu and Zn, speciation, agricultural soil